EMPOWERING GLOBAL LEARNERS WITH AI: A CROSS-CULTURAL WORKSHOP ON ACADEMIC INTEGRITY AND INNOVATION - Prihatiningtias, Yeney Widya; Atmini, Sari; Alam, Muhammad Dimar; Yuningsih, Yuni (Erudio Journal of Educational Innovation, 2025)
This international community engagement activity aimed to enhance international students’ ability to apply Artificial Intelligence (AI) tools for academic purposes. The mini-workshop, titled “Practical Use of AI Tools for Academic Purposes,” was held at Curtin University on Friday, October 2, 2025. The first session, presented by Muhammad Dimar Alam, M.Acc. from Universitas Brawijaya (Indonesia), demonstrated the use of various AI tools such as ChatGPT, Grammarly, and Litmaps for literature review, academic writing, data analysis, and scholarly communication. The second session, led by Yuni Yuningsih, Ph.D. from Curtin University, focused on Ethical Considerations and Academic Integrity of Generative AI, emphasizing responsible and ethical use of AI in higher education. Participants consisted of Curtin University international students from diverse national and disciplinary backgrounds. The workshop fostered cross-cultural collaboration, critical reflection, and creative engagement with emerging AI technologies in academic research and writing.